PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR MODAL - Wahyuni, Irma; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the influence of growth opportunity, profitability and dividend policy to the capitalstructure of manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2014 periods. Thepopulation is all manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2014periods and they have been selected by using purposive sampling, so 26 manufacturing companies which have metthe criteria have been selected as samples. The data analysis techniques has been done by using multiple regressionanalysis and the dependent variable is capital structure and the independent variables are growth opportunity,profitability and dividend policy by using SPSS. The result of goodness of fit test shows that growth opportunity,profitability and dividend policy are the explanatory factors from the capital structure. The result of determinationcoefficient test has proved that the independent variables give influence to the dependent variable. The result ofhypothesis test which has been done by using t test has proved that growth opportunity and profitability givesinfluence to the capital structure. Meanwhile, the dividend policy does not give any influence to the capitalstructure.Keywords: growth opportunity, profitability, dividend policy, capital structure.